Decreased SMG7 expression associates with lupus-risk variants and elevated antinuclear antibody production (2016)
Objectives Following up the systemic lupus erythematosus (SLE) genome-wide association studies (GWAS) identification of NMNAT2 at rs2022013, we fine-mapped its 150a €...kb flanking regions containing NMNAT2 and SMG7 in a 15a €...292 case-control multi-ancestry population and tested functions of identified variants. Methods We performed genotyping using custom array, imputation by IMPUTE 2.1.2 and allele specific functions using quantitative real-time PCR and luciferase reporter transfections. SLE peripheral blood mononuclear cells (PBMCs) were cultured with small interfering RNAs to measure antinuclear antibody (ANA) and cyto/chemokine levels in supernatants using ELISA. Results We confirmed association at NMNAT2 in European American (EA) and Amerindian/Hispanic ancestries, and identified independent signal at SMG7 tagged by rs2702178 in EA only (p=2.4×10 a '8, OR=1.23 (95% CI 1.14 to 1.32)). In complete linkage disequilibrium with rs2702178, rs2275675 in the promoter region robustly associated with SMG7 mRNA levels in multiple expression quantitative trait locus (eQTL) datasets. Its risk allele was dose-dependently associated with decreased SMG7 mRNA levels in PBMCs of 86 patients with SLE and 119 controls (p=1.1×10 a '3 and 6.8×10 a '8, respectively) and conferred reduced transcription activity in transfected HEK-293 (human embryonic kidney cell line) and Raji cells (p=0.0035 and 0.0037, respectively). As a critical component in the nonsense-mediated mRNA decay pathway, SMG7 could regulate autoantigens including ribonucleoprotein (RNP) and Smith (Sm). We showed SMG7 mRNA levels in PBMCs correlated inversely with ANA titres of patients with SLE (r=a '0.31, p=0.01), and SMG7 knockdown increased levels of ANA IgG and chemokine (C-C motif) ligand 19 in SLE PBMCs (p=2.0×10 a '5 and 2.0×10 a '4, respectively). Conclusion We confirmed NMNAT2 and identified independent SMG7 association with SLE. The inverse relationship between levels of the risk allele-associated SMG7 mRNAs and ANA suggested the novel contribution of mRNA surveillance pathway to SLE pathogenesis. © 2016 Published by the BMJ Publishing Group Limited.